APLIKASI E – KATALOG PERPUSTAKAAN BERBASIS MOBILE ANDROID - Fitriani Sahara; Rena Adriana (Jurnal Informatika Global)
Libraries were built and convened at the rationale to accommodate and storing all publications in and foreign are valuable in order to developof knowledge. The primary functioneach library is to hold, process, present and disseminate the information to user. In order tofulfill the functions of, the librariesshould becultivate andregulate the collection such thatinformation contained on the collection can be saved and retrieved be conveniently. One of the retrieval system is commonly recognizedin libraries is a library catalog. Through the a library catalog, user can access to a libraries collection. A library collections inform state ofit has resources to the user, via the catalog. In line withdevelopment of technologyformulation and accessing the catalog must be done online. The presentation of online catalog of allows user to access from the mobile device that further accelerate the process of delivering information.Keyword:retrieval system, catalog, libraries, online, mobile